La violence de l’aménagement japonais comme matrice du double : petit détour par l’exemple du manga Akira - Raphaël Languillon-Aussel (Ebisu: Études Japonaises)
The nature of Japanese urban planning and development is particularly violent. However, it is a form of violence that is often excused as part of the Japanese nature or the history of the country. This results in a degree of concealment of that violence. In response, we see the intense production of reality “doubles” – a form of hyper-reality – in popular and mass culture, including manga. This text analyzes the manga series Akira using notions of dystopia and concrete utopia to understand which assemblage of reality the violence of the manga doubles for.